A Solution of a Dispersion Problem for the Concentration of Pollutants in River Water - Bhandari, Prem Sagar (BMC Journal of Scientific Research, 2022)
In this study, one-dimensional advection dispersion equation is solved for the concentration of water pollutant. To solve the differential equation, the Laplace’s transform technique has been used assuming no added pollutants on the way of water along the river. From the study, it is found that for various time period and speed, the concentration of the water pollutants decreases continuously, as the distance of the river increases from the point source.